Subsidized and non-subsidized R&D projects: Do they differ? - Mila Koehler; Bettina Peters (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
Little is known about whether and to what extent the outcome of subsidized and non-subsidized R&D projects differ. In this paper we exploit a novel dataset of patent applications filed in Germany between 1995-2005, which allows us to identify if a patent application stems from a subsidized project or not. We use a variety of patent indicators to elucidate to what extent successful subsidized and non-subsidized R&D projects within the same firm differ. Results show that patent applications from subsidized R&D projects have a higher private value, are more often co-applied, more general, but less original, and have larger inventor teams when compared to all other patent applications filed by the same firms. These differences seem to reflect that thematic R&D programs aim to support collaborative R&D projects that have an immediate economic utilization of results.
urn:nbn:de:bsz:180-madoc-436105
Keywords: H25; H50; O31; O34; O38; 330; R&D; subsidies; patents; evaluation; project-level analysis; within firm comparison